Successful treatment of acute respiratory distress syndrome caused by hypervirulent Klebsiella pneumoniae with extracorporeal membrane oxygenation and continuous renal replacement therapy: A case report and literature review - Peng, Wenzhong; Wu, Yanhao; Lu, Rongli; Zheng, Yunpeng; Chen, Jie; Pan, Pinhua (Frontiers in Medicine, 2022)
Hypervirulent Klebsiella pneumoniae (hvKP) causes invasive infections and leads to high morbidity and mortality rates. Here, we report the case of a Chinese man with diabetes mellitus who developed acute respiratory distress syndrome and septic shock due to hvKP belonging to the K1 strain. The patient was treated with venovenous extracorporeal membrane oxygenation and continuous renal replacement therapy, in combination with antibiotics and recovered well. Clinicians should be aware of fatal infections caused by hvKP and investigate the best treatment options for patients at various stages of infection.